Warsaw ghetto police : the Jewish Order Service during the Nazi occupation - Person, Katarzyna (Cornell University Press, 2021)
"Focuses on the history of the Jewish Order Service (known as the Jewish Police) in the Warsaw Ghetto, 1940-1943 and its perception among ghetto inhabitants"